Preparation method of high-porosity iron phosphate

Through the preparation method of high porosity iron phosphate, the problem of unsatisfactory iron phosphate grinding performance is solved, and the performance and processing efficiency of lithium iron phosphate materials are improved, thereby reducing production costs.

CN119461292APending Publication Date: 2025-02-18GUIZHOU PHOSPHATE KAIRUI TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411952117.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The grinding performance of existing iron phosphate is not ideal, which affects the performance, processing efficiency and cost of lithium iron phosphate materials.

Method used

Using the preparation method of high porosity iron phosphate, by mixing ferrous sulfate with monoammonium phosphate, stirring and heating, and adding oxidizing agents and precipitating agents to react. After filtration, washing, aging and drying, additives such as cetyl trimethyl are added. Ammonium bromide, citric acid, and polyvinylpyrrolidone are calcined to form porous iron phosphate.

Benefits of technology

It significantly improves the grinding performance of iron phosphate, improves the performance and processing efficiency of lithium iron phosphate materials, and reduces energy consumption and costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461292A_ABST
    Figure CN119461292A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium battery positive electrode material preparation, and discloses a high-porosity iron phosphate preparation method, which comprises: 1, mixing ferrous sulfate and a monoammonium phosphate solution to obtain a mixed solution; 2, stirring and heating the mixed solution, and adding an oxidizing agent and a precipitating agent for reaction; after the reaction is finished, filtering and washing; step 3, heating and aging the filtered and washed filter cake, and then filtering, washing and drying to obtain iron phosphate dihydrate; 4, the iron phosphate dihydrate is smashed, an additive is added, calcination is conducted, porous iron phosphate is obtained, and the additive is at least one of cetyltrimethylammonium bromide, citric acid and polyvinylpyrrolidone. According to the invention, the additive is creatively added in the calcination stage of the iron phosphate, and the gasification of the additive in the calcination stage enables multiple pores to appear on the surface of the iron phosphate, which is beneficial for greatly improving the grinding efficiency and reducing the energy consumption and the cost in the grinding stage of preparing the lithium iron phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium battery positive electrode material preparation, and in particular to a method for preparing high-porosity iron phosphate. Background Art

[0002] Lithium iron phosphate battery is a lithium-ion battery whose positive electrode material is mainly composed of lithium iron phosphate (LiFePO4). Compared with other types of lithium-ion batteries, such as lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4) and nickel cobalt manganese ternary materials (NMC), LFP batteries have higher safety, longer cycle life and better thermal stability.

[0003] Iron phosphate (FePO4) is a white to light yellow powder solid, which is insoluble in water and easily soluble in acidic solution to form soluble ferrous salts. As a precursor of lithium iron phosphate, iron phosphate not only determines the quality and performance of the final product, but also directly affects the production process and technical and economic indicators. According to different synthesis methods, iron phosphate can be divided into two forms: amorphous iron phosphate and crystalline iron phosphate, of which the latter is more commonly used. At present, the preparation methods of iron phosphate in industry usually include:

[0004] 1. Co-precipitation method: A mixed solution containing an iron source (such as ferrous sulfate), a phosphorus source (such as phosphoric acid or phosphate) and other auxiliary components (such as surfactants) is reacted under specific conditions to generate uniformly dispersed iron phosphate particles.

[0005] 2. Solid-phase reaction method: After the iron source, phosphorus source and carbon source are fully mixed by mechanical ball milling or other methods, they are calcined at high temperature to induce a chemical reaction between them to generate iron phosphate.

[0006] 3. Sol-gel method: Use organic metal compounds or inorganic salts as raw materials to form a sol system in an appropriate solvent, and then obtain nano-scale iron phosphate powder through steps such as drying and sintering.

[0007] 4. Microwave-assisted synthesis: Microwave heating technology is used to accelerate the reaction process, shorten the preparation time, and effectively control the particle size distribution of the product.

[0008] In order to ensure the performance of the subsequent lithium iron phosphate material, the iron phosphate needs to be fully ground to ensure the complete reaction. However, the grinding performance of the iron phosphate obtained by the above preparation method is not ideal, and the grinding property of iron phosphate will directly affect the performance of lithium iron phosphate as well as the efficiency and cost of processing. Therefore, it is urgent to develop a new preparation process that can improve the grinding performance of iron phosphate. Summary of the invention

[0009] The present invention aims to provide a method for preparing high-porosity iron phosphate to improve the grinding performance of the iron phosphate.

[0010] To achieve the above object, the present invention adopts the following technical solution: a method for preparing high-porosity iron phosphate, comprising the following steps:

[0011] Step 1, mixing ferrous sulfate and monoammonium phosphate solution to obtain a mixed solution;

[0012] Step 2, stirring the mixed solution, heating it, and adding an oxidant and a precipitant to react; filtering and washing after the reaction is completed;

[0013] Step 3: filtering and washing the filter cake, heating it for aging, and then filtering, washing, and drying it to obtain ferric phosphate dihydrate;

[0014] Step 4: crush the ferric phosphate dihydrate, add an additive and then calcine to obtain porous ferric phosphate, wherein the additive is at least one of hexadecyltrimethylammonium bromide, citric acid and polyvinylpyrrolidone.

[0015] Preferably, as an improvement, in step 1, the iron concentration in the ferrous sulfate solution is 5-6%; the phosphorus concentration in the monoammonium phosphate solution is 3-4%; and the phosphorus-iron molar ratio of the mixed solution is 1.04-1.17.

[0016] Preferably, as an improvement, in step one, the preparation method of ferrous sulfate solution is: prepare ferrous phosphate heptahydrate, a by-product of titanium dioxide, into a solution, add an impurity remover and stir at 45-55°C for 0.5-1h, then filter to obtain a purified ferrous sulfate solution, and add acid to adjust the pH to obtain a purified ferrous sulfate solution.

[0017] Preferably, as an improvement, the impurity remover is at least one of phosphoric acid, ammonia water, and sodium hydroxide.

[0018] Preferably, as an improvement, the acid used to adjust the pH is at least one of sulfuric acid and phosphoric acid, and the added ratio of the acid is 0.1-5% of the mass of ferrous sulfate.

[0019] Preferably, as an improvement, in step 2, the stirring speed is 300-400 rpm, and the heating temperature is 40-65°C.

[0020] Preferably, as an improvement, in step 2, the oxidant is hydrogen peroxide, which is added in excess at a molar ratio of 30-50%; the precipitant is at least one of ammonia water, sodium hydroxide, and ammonium bicarbonate, the reaction pH is 1.8-2.2, and the reaction time is 0.5-2h.

[0021] Preferably, as an improvement, in step three, the aging temperature is 80-100°C, and the holding time after aging and whitening is 0.5-4h; the drying temperature is 60-180°C, and the drying time is based on the moisture content ≤20%.

[0022] Preferably, as an improvement, in step 2 and step 3, the washing water is at least one of deionized water, washing water recycling water, and distilled recycling water, and the amount of washing water added is 2-8 times the mass of the filter cake.

[0023] Preferably, as an improvement, in step four, the concentration of the additive is 5-20%, and the spraying amount is 1-5%; the calcination is a two-step calcination, and the calcination conditions are 150-200℃ for 0.5h, then heated to 550℃-650℃, and calcined for 1-4h.

[0024] The principles and advantages of this solution are:

[0025] 1. This technical solution creatively adds additives during the calcination stage of iron phosphate. The gasification of the additives during the calcination stage can cause porous surfaces on the surface of the iron phosphate, which is beneficial to greatly improve the grinding efficiency and reduce energy consumption and costs during the grinding stage of preparing lithium iron phosphate.

[0026] 2. In this technical solution, after determining the technical solution for spraying additives, the additive spraying time is optimized and the additive is sprayed on the dried ferric phosphate, so that the additive does not enter the wastewater treatment system, effectively reducing the treatment of production wastewater.

[0027] 3. In this technical solution, by optimizing the type, concentration and spraying amount of additives, the porosity and pore uniformity of the prepared iron phosphate can be guaranteed, and the specific surface area of ​​the material can be guaranteed. Experiments show that polyvinyl pyrrolidone is the best additive with the best pore-forming effect.

[0028] 4. The process steps of this technical solution are simple and easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a SEM image of the iron phosphate obtained in Example 1.

[0030] Figure 2 This is a SEM image of the iron phosphate obtained in Comparative Example 1.

[0031] Figure 3 This is a SEM image of the iron phosphate obtained in Comparative Example 2.

[0032] Figure 4 This is a SEM image of the iron phosphate obtained in Comparative Example 3. DETAILED DESCRIPTION

[0033] The following is further described in detail through specific implementations, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the technical means used in the following implementations are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; the materials, reagents, etc. used can all be obtained from commercial channels.

[0034] Program Overview:

[0035] A method for preparing high-porosity iron phosphate comprises the following steps:

[0036] Step 1: prepare a solution of ferrous phosphate heptahydrate produced as a byproduct of titanium dioxide, wherein the iron concentration of the solution is 5-6%; add an impurity remover and stir at 45-55°C for 0.5-1h, then filter to obtain a purified ferrous sulfate solution, and add acid to adjust the pH to obtain a purified ferrous sulfate solution; the impurity remover is at least one of phosphoric acid, ammonia water, and sodium hydroxide; the acid used to adjust the pH is at least one of sulfuric acid and phosphoric acid, and the acid addition ratio is 0.1-5% of the mass of ferrous sulfate. Prepare an industrial-grade monoammonium phosphate solution, wherein the phosphorus concentration is 3-4%, and mix the monoammonium phosphate with ferrous sulfate to obtain a mixed solution, wherein the phosphorus-iron molar ratio of the mixed solution is 1.04-1.17.

[0037] Step 2: Heat the mixed solution to 40-65°C and stir at a stirring speed of 300-400rpm. After the solution reaches the set temperature, add an oxidant (hydrogen peroxide) for oxidation. Hydrogen peroxide is added at a molar excess of 30-50%. Then, add a precipitant (the precipitant is at least one of ammonia water, sodium hydroxide, and ammonium bicarbonate) to raise the pH to between 1.8 and 2.2. The reaction is complete and the reaction time is 0.5-2h. After the reaction is completed, wash twice and filter three times to obtain a reaction cake. The washing water is at least one of deionized water, washing water, and distilled water. The amount of washing water added is 2-8 times the mass of the wet cake of the reaction material.

[0038] Step 3: Add water to the reaction filter cake and stir it for aging at a temperature of 80-100°C according to the solid content of the reaction filter cake of 15%-40%, and the holding time after aging and whitening is 0.5-4h. After aging, filter and wash, the washing water is 2-8 times the mass of the filter cake, the washing water is deionized water, and the washing times are 1-2 times; the washed filter cake is dried to obtain dihydrate iron phosphate, the drying temperature is 60-180°C, and the drying time is based on the moisture content ≤20%.

[0039] Step 4: Grind and crush the dried ferric phosphate dihydrate, and spray an additive after crushing. The additive is at least one of cetyltrimethylammonium bromide (CTAB), citric acid, and polyvinyl pyrrolidone. The concentration of the additive is 5-20%, and the spraying amount is 1-5%. The sample sprayed with the additive is calcined in two steps. The calcination conditions are 150-200°C for 0.5h, then the temperature is raised to 550°C-650°C, and calcined for 1-4h to obtain battery-grade porous iron phosphate.

[0040] Example 1

[0041] A method for preparing high-porosity iron phosphate comprises the following steps:

[0042] Step 1: prepare a solution of ferrous phosphate heptahydrate produced as a byproduct of titanium dioxide, wherein the iron concentration of the solution is 5%; add an impurity remover and stir at 55°C for 0.5h, then filter to obtain a purified ferrous sulfate solution, and add acid to adjust the pH to obtain a purified ferrous sulfate solution; the impurity remover is phosphoric acid; the acid used to adjust the pH is sulfuric acid, and the acid addition ratio is 5% of the mass of ferrous sulfate. Prepare an industrial-grade monoammonium phosphate solution, wherein the phosphorus concentration is 4%, and mix the monoammonium phosphate with ferrous sulfate to obtain a mixed solution, wherein the phosphorus-iron molar ratio of the mixed solution is 1.17.

[0043] Step 2: Heat the mixed solution to 65°C and stir at 400rpm. After the solution reaches the set temperature, add the oxidant (hydrogen peroxide) for oxidation. Hydrogen peroxide is added in a molar excess of 50%, and then add the precipitant (ammonium bicarbonate) to raise the pH to 2.2. The reaction is complete and the reaction time is 2h. After the reaction is completed, wash twice and filter three times to obtain the reaction cake. The washing water is deionized water, and the amount of washing water added is 8 times the mass of the wet cake of the reaction material.

[0044] Step 3: Add water to the reaction filter cake and stir it for aging at a temperature of 80°C according to the solid content of the reaction filter cake being 40%, and the holding time after aging and whitening being 4h. After aging, filter and wash the filter cake, the washing water is 8 times the mass of the filter cake, the washing water is deionized water, and the washing times are 1-2 times; the washed filter cake is dried to obtain dihydrate ferric phosphate, the drying temperature is 60°C, and the drying time is based on the moisture content ≤20%.

[0045] Step 4: Grind and crush the dried ferric phosphate dihydrate, and then spray the additive in the form of mist. The additive is polyvinyl pyrrolidone, the concentration of the additive is 20%, and the spraying amount is 1%; calcine the sample after spraying the additive, and the calcination is divided into two steps. The calcination conditions are 150°C for 0.5h, then raised to 650°C, and calcined for 1h to obtain battery-grade porous iron phosphate.

[0046] Example 2

[0047] A method for preparing high-porosity iron phosphate comprises the following steps:

[0048] Step 1: prepare a solution of ferrous phosphate heptahydrate produced as a byproduct of titanium dioxide, wherein the iron concentration of the solution is 6%; add an impurity remover and stir at 45°C for 1 hour, then filter to obtain a purified ferrous sulfate solution, and add acid to adjust the pH to obtain a purified ferrous sulfate solution; the impurity remover is phosphoric acid; the acid used to adjust the pH is phosphoric acid, and the addition ratio of the acid is 2% of the mass of ferrous sulfate. Prepare an industrial-grade monoammonium phosphate solution, wherein the phosphorus concentration is 3%, and mix the monoammonium phosphate with ferrous sulfate to obtain a mixed solution, wherein the phosphorus-iron molar ratio of the mixed solution is 1.04.

[0049] Step 2: Heat the mixed solution to 40°C and stir at 300rpm. After the solution reaches the set temperature, add the oxidant (hydrogen peroxide) for oxidation. Hydrogen peroxide is added at a molar excess of 30%, and then add the precipitant (ammonium bicarbonate) to raise the pH to 1.8. The reaction is complete and the reaction time is 2h. After the reaction is completed, wash twice and filter three times to obtain the reaction cake. The washing water is deionized water, and the amount of washing water added is 8 times the mass of the wet cake of the reaction material.

[0050] Step 3: Add water to the reaction filter cake and stir it for aging at a temperature of 15%, the solid content of the reaction filter cake is 15%, the aging temperature is 100°C, and the holding time after aging and whitening is 2.5h. After aging, filter and wash, the washing water is 8 times the mass of the filter cake, the washing water is deionized water, and the washing times are 1-2 times; the washed filter cake is dried to obtain dihydrate iron phosphate, the drying temperature is 120°C, and the drying time is based on the moisture content ≤20%.

[0051] Step 4: Grind and crush the dried ferric phosphate dihydrate, and then spray the additive in the form of mist. The additive is polyvinyl pyrrolidone, the concentration of the additive is 10%, and the spraying amount is 5%; calcine the sample after spraying the additive, and the calcination is divided into two steps. The calcination conditions are 200°C for 0.5h, then the temperature is raised to 550°C, and calcined for 4h to obtain battery-grade porous iron phosphate.

[0052] Comparative Example 1

[0053] The difference between this comparative example and Example 1 is that in this comparative example, no additive spraying is performed before calcination in step 4.

[0054] Comparative Example 2

[0055] The difference between this comparative example and Example 1 is that in this comparative example, in step 4, the additive added is trimethylammonium bromide.

[0056] Comparative Example 3

[0057] The difference between the comparative example and Example 1 is that in this comparative example, in step 4, the additive added is citric acid.

[0058] Comparative Example 4

[0059] The difference between this comparative example and Example 1 is that in this comparative example, in step 4, the concentration of the additive is 25%.

[0060] Comparative Example 5

[0061] The difference between this comparative example and Example 1 is that in this comparative example, in step 4, the spraying amount of the additive is 6%.

[0062] Comparative Example 6

[0063] The difference between this comparative example and Example 1 is that in this comparative example, in step 4, the calcination condition is calcination at 500 degrees Celsius for 4 hours.

[0064] Experimental Example 1

[0065] The iron phosphate prepared in Example 1 and Comparative Examples 1-3 was scanned by electron microscope, and the results were as follows: Figure 1-4 As shown, it can be seen from the results that the iron phosphate prepared in Example 1 of the present invention has more pores on the surface, while the iron phosphate obtained in Comparative Examples 1-3 has fewer pores on the surface.

[0066] Experimental Example 2

[0067] The physical and chemical properties of the iron phosphate prepared in the above embodiments and comparative examples were analyzed, and the detection indicators and data results are shown in Table 1. The results show that the Fe content, P content, Fe / P and other metal element contents of the iron phosphate prepared in Example 1 of the present invention meet the corresponding standard requirements, and the specific surface area is large.

[0068] Table 1

[0069]

[0070]

[0071] Note: “ND” means not detected.

[0072] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing high-porosity iron phosphate, characterized in that: The steps include: Step 1, mixing ferrous sulfate and monoammonium phosphate solution to obtain a mixed solution; Step 2, stirring the mixed solution, heating it, and adding an oxidant and a precipitant to react; filtering and washing after the reaction is completed; Step 3: filtering and washing the filter cake, heating it for aging, and then filtering, washing, and drying it to obtain ferric phosphate dihydrate; Step 4: crush the ferric phosphate dihydrate, add an additive and then calcine to obtain porous ferric phosphate, wherein the additive is at least one of hexadecyltrimethylammonium bromide, citric acid and polyvinylpyrrolidone.

2. The method for preparing high-porosity ferric phosphate according to claim 1, characterized in that: In step 1, the iron concentration in the ferrous sulfate solution is 5-6%; the phosphorus concentration in the monoammonium phosphate solution is 3-4%; and the phosphorus-iron molar ratio of the mixed solution is 1.04-1.

17.

3. The method for preparing high-porosity ferric phosphate according to claim 2, characterized in that: In step 1, the preparation method of ferrous sulfate solution is as follows: ferrous phosphate heptahydrate produced as a by-product of titanium dioxide is prepared into a solution, an impurity remover is added and stirred at 45-55° C. for 0.5-1 h, and then filtered to obtain a purified ferrous sulfate solution, and an acid is added to adjust the pH to obtain a purified ferrous sulfate solution.

4. The method for preparing high-porosity ferric phosphate according to claim 3, characterized in that: The impurity remover is at least one of phosphoric acid, ammonia water and sodium hydroxide.

5. The method for preparing high-porosity ferric phosphate according to claim 4, characterized in that: The acid used to adjust the pH is at least one of sulfuric acid and phosphoric acid, and the added proportion of the acid is 0.1-5% of the mass of ferrous sulfate.

6. The method for preparing high-porosity ferric phosphate according to claim 5, characterized in that: In step 2, the stirring speed is 300-400 rpm, and the heating temperature is 40-65°C.

7. The method for preparing high-porosity ferric phosphate according to claim 6, characterized in that: In step 2, the oxidant is hydrogen peroxide, which is added in excess at a molar ratio of 30-50%; the precipitant is at least one of ammonia water, sodium hydroxide, and ammonium bicarbonate, the reaction pH is 1.8-2.2, and the reaction time is 0.5-2h.

8. The method for preparing high-porosity ferric phosphate according to claim 7, characterized in that: In step 3, the aging temperature is 80-100° C., and the holding time after aging and whitening is 0.5-4 hours; the drying temperature is 60-180° C., and the drying time is based on the moisture content ≤ 20%.

9. The method for preparing high-porosity ferric phosphate according to claim 8, characterized in that: In step 2 and step 3, the washing water is at least one of deionized water, washing water recycling water, and distilled recycling water, and the amount of washing water added is 2-8 times the mass of the filter cake.

10. The method for preparing high-porosity ferric phosphate according to claim 9, characterized in that: In step 4, the concentration of the additive is 5-20%, and the spraying amount is 1-5%; the calcination is a two-step calcination, and the calcination conditions are 150-200°C for 0.5h, then heated to 550°C-650°C, and calcined for 1-4h.

Citation Information

Cited By

  • Anhydrous ferric phosphate, its preparation method and application

    CN120736490B